Melioidosis and glanders modulation of the innate immune system: barriers to current and future vaccine approaches. (1st September 2016) - Aschenbroich, Sophie A.; Lafontaine, Eric R.; Hogan, Robert J.
ABSTRACT: Burkholderia pseudomallei and Burkholderia mallei are pathogenic bacteria causing fatal infections in animals and humans. Both organisms are classified as Tier 1 Select Agents owing to their highly fatal nature, potential/prior use as bioweapons, severity of disease via respiratory exposure, intrinsic resistance to antibiotics, and lack of a current vaccine. Disease manifestations range from acute septicemia to chronic infection, wherein the facultative intracellular lifestyle of these organisms promotes persistence within a broad range of hosts. This ability to thrive intracellularly is thought to be related to exploitation of host immune response signaling pathways. There are currently considerable gaps in our understanding of the molecular strategies employed by these pathogens to modulate these pathways and evade intracellular killing. A better understanding of the specific molecular basis for dysregulation of host immune responses by these organisms will provide a stronger platform to identify novel vaccine targets and develop effective countermeasures.